Specific Learning Disability Identification in an RtI Method: Do Measures of Cognitive Ability Matter?. Issue 4 (16th September 2022) - Hajovsky, Daniel B.; Maki, Kathrin E.; Chesnut, Steven R.; Barrett, Courtenay A.; Burns, Matthew K.
Abstract: This study examined the extent to which cognitive ability index scores predicted multidisciplinary teams' (MDT) SLD identification within a response‐to‐intervention (RtI) method after accounting for RtI slope and norm‐referenced achievement scores. Results showed that four achievement composite scores (i.e., basic reading, reading comprehension, math computation, and math problem solving) and two cognitive ability index scores (i.e., crystallized ability, working memory) predicted MDT‐determined SLD, explaining 81% of the variance. The inclusion of academic achievement and cognitive ability index scores predicted MDT‐determined SLD with 90% accuracy; cognitive ability index scores only increased specificity (sensitivity = 95%; specificity = 79%). RtI slope did not predict MDT‐determined SLD, which was a required component of the evaluation.